Knowledge and economic conduct : the social foundations of the modern economy - Stehr, Nico (Studies in comparative political economy and public policy., 2002)
"Examining the foundations of the modern capitalist economy from a broad social scientific perspective, this challenging work posits that changing economic circumstances - namely, an end to the primacy of labour and property as determinants of prosperity - have created a need for a new theoretical platform, one that transcends standard economic discourse." "In Nico Stehr's view, knowledge is now the most significant source of economic growth - the 'prime productive factor.' This shift to a knowledge-based society, however, is a source of some uncertainty and apprehension. Will it bring a more sustainable, less ecologically disruptive form of production, or escalating levels of unemployment? What are the practical social, political, and economic implications of the new technology? What are the possibilities for social action in a context where such possibilities are being limited? Stehr proposes that a new social science agenda is needed to address these and other urgent questions arising from the new economic realities." "Knowledge and Economic Conduct is essential reading for students and social scientists with an interest in technology, globalization, and the changing economy, as well as for researchers and policy makers within both the public and private sectors."--Jacket